Living faith online: a phenomenological study of digital spirituality, spiritual coping, and psychological distress among muslim university students - Miftahuddin Miftahuddin; Muhamad Hasbi (RedWhite Press, 2024)
This study asks a deceptively simple question: when Muslim university students in Pekanbaru feel anxious, overwhelmed, or spiritually adrift, where do they turn and what does that turning mean to them? Adopting a hermeneutic phenomenological design, the study examines the lived experience of digital spirituality as a resource for spiritual coping and psychological distress among Generation Z Muslim students. In-depth, semi-structured interviews were conducted with 120 Muslim university students and five Islamic counseling lecturers (Dosen BK Islam), with interpretive analysis supported by NVivo 12 and strengthened through source, investigator, and method triangulation. Rather than treating digital religious content as mere media consumption, the analysis attends to how students describe, feel, and make sense of these encounters. The findings reveal that digital spirituality is experienced as an immediate and portable form of psychological first aid, as a distributed sense of the sacred that loosens the boundary between mosque and dormitory, and as an arena in which religious identity is tested and validated. Yet the same digital environment that consoles also wounds: participants described religious guilt during periods of low practice, a distinct form of spiritual burnout, and comparison-driven anxiety produced by curated displays of piety. These tensions consolation and pressure, autonomy and validation-seeking constitute the essential structure of the experience. The study contributes a phenomenologically grounded account of how faith is lived online, and argues that Islamic counseling in Indonesian higher education must extend into digital space, equip counselors with digital and media-critical literacy, and learn to address spiritual distress without pathologizing religious commitment.